O group is a protective factor for COVID19 in Basque population. - Maider Muñoz-Culla; Andres Roncancio-Clavijo; Bruno Martínez; Miriam Gorostidi-Aicua; Luis Piñeiro; Arkaitz Azkune; Ainhoa Alberro; Jorge Monge-Ruiz; Tamara Castillo-Trivino; Alvaro Prada; David Otaegui (PLoS ONE)
ABO blood groups have recently been related to COVID19 infection. In the present work, we performed this analysis using data from 412 COVID19 patients and 17796 blood donors, all of them from Gipuzkoa, a region in Northern Spain. The results obtained confirmed this relation, in addition to showing a clear importance of group O as a protective factor in COVID19 disease, with an OR = 0.59 (CI95% 0.481-0.7177, p<0.0001) while A, B and AB are risk factors. ABO blood groups are slightly differently distributed in the populations and therefore these results should be replicated in the specific areas with a proper control population.